The Assessment of Androgenic Response of Two Nematode Resistant Pepper (Capsicum annuum L.) Genotypes - Flavien Shimira; Davut Keleş; Hatıra Taşkın; Kazım Abak (Turkish Journal of Agriculture: Food Science and Technology)
Pepper is one of the most cultivated vegetables worldwide and also consumed substantially as a flavouring ingredient in different culinary traditions. Therefore, many researchers have focused on its breeding to develop new varieties. One of plant breeding aims is to attain disease and pest resistance. The use of tissue culture methods in plant breeding has many advantages. The response of two nematode resistant pepper genotypes to the anther culture and the effect of cold pre-treatment to the floral buds have been investigated in this study. Alata 2095 and Alata 2096 both specified as resistant to the nematode by Alata Horticultural Research Institute (Alata, Mersin, Turkey) were used as plant material. Two pre-treatments were used in this study: cold and no cold. In cold treatment, flower buds were kept in fridge at 4°C for 24 hours prior to the anther culture. Murashige and Skoog medium contained 0.25% activated charcoal, 6.5 g L-1 agar, 0.5 mg L-1 6-benzyl-amino-purine (BAP), 4 mg L-1 naphthalene-acetic-acid (NAA), 15 mg L-1 silver nitrate (AgNO3), and 30 g L-1 sucrose was used. After assessment, the highest mean of plant number was 39.08 per 100 anthers for Alata 2095 genotype. It was 46.61 and 31.56 in cold and no cold treatment, respectively. For Alata 2096 genotype, the mean was 1.96 per 100 anthers (1.68 and 2.25 in cold and no cold treatment, respectively). Statistical analyses confirmed that there was significant difference between treatments, genotypes and also significant interaction between those factors. At the end of the study, we can say that Alata 2095 genotype has a good androgenic response and it can be beneficial in further pepper breeding studies.